Autosomal dominant sacral agenesis: Currarino syndrome. Issue 8 (1st August 2000) - Lynch, Sally Ann; Wang, Yiming; Strachan, T; Burn, John; Lindsay, Susan
Abstract : Autosomal dominant sacral agenesis is characterised by a partial agenesis of the sacrum typically involving sacral vertebrae S2-S5 only. Associated features include anorectal malformation, a presacral mass, and urogenital malformation. Together, these features have been defined as the Currarino syndrome. Recently, HLXB9 has been identified as the major causative gene in Currarino syndrome allowing identification of asymptomatic heterozygotes. In this review, we have performed an analysis of medical publications, and our own additional cases, to identify the range of malformations and complications that occur. We have also estimated risks of malformation in heterozygotes by using Weinburg's proband method on families personally known to us in order to provide accurate genetic counselling information.